PET imaging of DNA damage using 89Zr-labelled anti-γH2AX-TAT immunoconjugates - Knight, J; Topping, C; Mosley, M; Kersemans, V; Falzone, N; Falzone, N; Fernández-Varea, J; Cornelissen, B (2015)
© 2015, Springer-Verlag Berlin Heidelberg. Purpose: The efficacy of most anticancer treatments, including radiotherapy, depends on an ability to cause DNA double-strand breaks (DSBs). Very early during the DNA damage signalling process, the histone isoform H2AX is phosphorylated to form γH2AX. With the aim of positron emission tomography (PET) imaging of DSBs, we synthesized a 89Zr-labelled anti-γH2AX antibody, modified with the cell-penetrating peptide, TAT, which includes a nuclear localization sequence. Methods: 89Zr-anti-γH2AX-TAT was synthesized using EDC/NHS chemistry for TAT peptide linkage. Desferrioxamine conjugation allowed labelling with 89Zr. Uptake and retention of 89Zr-anti-γH2AX-TAT was evaluated in the breast adenocarcinoma cell line MDA-MB-468 in vitro or as xenografts in athymic mice. External beam irradiation was used to induce DSBs and expression of γH2AX. Since 89Zr emits ionizing radiation, detailed radiobiological measurements were included to ensure 89Zr-anti-γH2AX-TAT itself does not cause any additional DSBs. Results: Uptake of 89Zr-anti-γH2AX-TAT was similar to previous results using 111In-anti-γH2AX-TAT. Retention of 89Zr-anti-γH2AX-TAT was eightfold higher at 1 h post irradiation, in cells expressing γH2AX, compared to non-irradiated cells or to non-specific IgG control. PET imaging of mice showed higher uptake of 89Zr-anti-γH2AX-TAT in irradiated xenografts, compared to non-irradiated or non-specific controls (12.1 ± 1.6 vs 5.2 ± 1.9 and 5.1 ± 0.8 %ID/g, respectively; p < 0.0001). The mean absorbed dose to the nucleus of cells taking up 89Zr-anti-γH2AX-TAT was twofold lower compared to 111In-anti-γH2AX-TAT. Additional exposure of neither irradiated nor non-irradiated cells nor tissues to 89Zr-anti-γH2AX-TAT resulted in any significant changes in the number of observable DNA DSBs, γH2AX foci or clonogenic survival. Conclusion: 89Zr-anti-γH2AX-TAT allows PET imaging of DNA DSBs in a tumour xenograft mouse model.